Results of Using Modified Early Warning Scores (MEWS) on The Incidence of Unplanned Transfer to CCU and ICCU in Patients Undergoing Percutaneous Coronary Intervention in Cardiac Catheterization Lab at Central Chest Institute of Thailand. - Thanaphatsorn, ์Nutchapuk; Puthaaroon, Benyapa (Journal of The Royal Thai Army Nurses, 2025)
This study aims to compare the outcomes of using traditional assessment methods versus the Modified Early Warning Score (MEWS) in predicting unplanned transfers to CCU and ICCU, in patients undergoing PCI in Cardiac Catheterization Lab at Central Chest Institute of Thailand. This study is quasiexperimental. Research conducted with a selected sample group of 160 people was divided into two groups: an experimental group using MEWS assessment and monitoring guidelines, and a control group using conventional assessment, each with 80 participants. The research instruments included MEWS guidelines and a structured record format for unplanned transfers to CCU and ICCU. Data analysis used descriptive statistics, Chi-Square tests and Fisher’s Exact test. The findings of the outcomes revealed that the experimental group experienced incidents of transfer to CCU and ICCU in 6 cases (7.5%). This was significantly lower than the control group, experienced incidents of transfer to CCU and ICCU in 15 cases (18.7%), with a statistically significant difference (P < .05). From the study, it is evident that Modified Early Warning Score guidelines effectively monitor postoperative patients after PCI before they deteriorate.